Powtoon as Interactive Media for Learning Arabic in Society 5.0 Era - Massofia, Fitrah Dinanti; Yolanda, Refiyana (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Learning Arabic has a very important role in improving language skills in Indonesian Madrasah. So that in order to support student success in learning Arabic, the teacher has role in presenting material that is packaged through the media to accommodate various student learning styles. So one of the teacher’s strategies in facing the era of society 5.0 is to create interactive learning using Powtoon media. This study aimed to analyze Powtoon media and its advantages and disadvantages in learning Arabic. This study uses a qualitative approach with the library research method and the data source from exploring the literature through the Powtoon website. In this study, data analysis followed the Miles and Huberman model approach, consisting of data display, data reduction, data presentation, and drawing conclusions. The study results show that: 1) Powtoon media has an attractive design, namely in designing material in the form of Arabic animation. So that it can help teachers and students learn Arabic better and more fun. 2) learning Arabic for middle-level students does not only rely on difficult textbooks but can be created using animations from Powtoon interactive media.